Efeito da proteína HSP70 de Mycobacterium tuberculosis na resposta pulmonar alérgica em camundongos - Barbosa, Gustavo Leivas (2012)
Introduction: Heat shock proteins like mycobacterial HSP70 has a protective and anti-inflamatory activity in several animals models diseases, like arthritis and skin allograft. This protein can modulates both the innate and adaptative immune system. Objective: The aim of this study was evaluate the effect of HSP70 from M. tuberculosis on development of pulmonary allergic reponse in a mice model. Methods: Female BALBc mice with ovalbumin induced pulmonary disease received intraperitoneal inject or intranasal instillation of mycobacterium HSP70. Treg cell in lung tissue, inflammatory cells profiles and cytokines levels in broncalveolar lavage fluid was measured. Results: HSP70 show an inhibitory effect on pulmonary allergic response on mice. Eosinophils, IL-5 and IFN- levels was reduced in broncoalveolar lavage fluid in animals that received intranasal instillation of mycobacterial HSP70. Conclusion: Mycobacterial HSP70 can be efficiently used to treat airway allergic disorders.